Impact of Static Var Compensator (SVC) Installation in Power System Stability - Ali Nasir, Mohamed Saleh; Jumaat, Siti Amely (Journal of Electronic Voltage and Application, 2020)
The research is proposed the modeling and analysis of Static Var Compensator (SVC) for stability improvement in power system. This is achieved by modeling a test system 220kV, 50Hz, and 100KVA base in long transmission line. Furthermore, the MATLAB/Simulink software is used to modeling the system in the normal condition and the fault condition of test system. The simulation results demonstrate the effectiveness and robustness of the proposed SVC on stability improvement in power system.